Photobiomodulation increases uprighting tooth movement and modulates IL‐1β expression during orthodontically bone remodeling - Murakami‐Malaquias‐Silva, Felipe; Perim Rosa, Ellen; Malavazzi, Tainá Caroline Santos; Silva, Tamiris; Santana Sarmento, Dmitry José; Garcez, Aguinaldo Silva; Fernandes, Marcella Ueda R.; Tortamano, Andre; Ramalho, Karen Muller; Motta, Lara Jansiski; Fernandes, Kristianne Porta Santos; Bussadori, Sandra Kalil; et al. (Journal of biophotonics, 2023)
This study investigated the effects of photobiomodulation (PBM) in acceleration of orthodontic movement of inferior molar uprighting movement. Thirty‐four individuals, with indication of molar uprighting movement for oral rehabilitation, were randomly divided in two groups: verticalization + PBM (808 nm, 100 mW, 1 J per point, 10 points and 25 J/cm2) or verticalization + PBM simulation. Elastomeric chain ligatures were changed every 30 days for 3 months. FBM was performed immediately, 24 h, 72 h, 1 and 2 months after activation. The primary outcome was the amount of uprighting movement. Secondary outcomes were pain, amount of medication, OHIP‐14 questionnaire, and cytokine IL‐1β. PBM group increase uprighting movement when compared to control after 3 months and modulate IL‐1β expression. For pain control, the amount of medication and OHIP‐14 no difference were found. This study suggests that PBM accelerates tooth movement during molar uprighting, due to modulation of IL‐1β during bone remodeling. The loss of a tooth can move adjacent and the antagonist teeth, which makes difficult prosthetic rehabilitation. Anchorage systems, such as mini‐implants, have been increasingly used as a treatment option. Recent studies have shown that photobiomodulation (PBM) can accelerate the orthodontic movement and decrease pain in intrusion movement. The aim of this study was to evaluate the effect of PBM on the acceleration of orthodontic movement of molar intrusion and its effect on pain and inflammation of periodontal tissues. Results show that photobiomodulation has increased uprighting tooth movement and also modulates IL‐1β expression during orthodontically bone remodeling.